Election Cycles in MPs' Outside Interests? The UK House of Commons, 2005–2010. (12th June 2012) - Geys, Benny
<x xml:space="preserve">Abstract</x> Politicians often implement popular changes in public policies prior to elections, with the aim of improving their Election Day outcome. This research note evaluates whether such 'electioneering' carries over also into politicians' extra‐parliamentary activities. Evidence from the UK House of Commons over the period 2005–10 suggests that adjustments do occur in MPs' outside activities over the election cycle. The safety of the politician's seat and his or her decision to stand for re‐election play an important mediating role.